Un Grec au service de Sa Majesté - Mathieu Couderc (Diasporas: Circulations, Migrations, Histoire)
The purpose of this article is to explore foreignness as a condition of social climbing in the French 16th century. Demetrios Palaiologos was a Greek interpreter, merchant and officer who served King Francis I of France between 1533 and 1560. His life is still largely ignored by the historiography. Demetrios first acted as a broker between the French and Ottoman diplomacy in the 1530s, serving the French as an intercessor and diplomatic agent. Thanks to these first activities, Demetrios stayed at the king’s service and settled himself in Paris as a curial officer of His Majesty and a Parisian bourgeois by marriage into an influential family, the Vitrys. There, Demetrios was identified alternately as a bourgeois, a merchant, an officer, and, sometimes, as a Greek, but never as a foreigner. This work shows that the classic historiography, which conceptualizes the building of Modern state in Modern Europe as an administrative process of rationalization by the power of the Prince, must be discussed. Indeed, when the French kings wanted to negotiate with the Ottomans, they couldn’t find any interpreter. So Francis I and his successors chose to employ some people who were not really their subjects but were coming from Eastern Mediterranean, being for sale as brokers. These people, like Demetrios Palaiologos, served their masters and themselves. As an interpreter, Demetrios succeeded to serve the king, enter the French Court, and get money. As an officer at the Court, he got influence… and money. As a merchant, he got influence on the Parisian Bourgeoisie... and money. As a rich man, Demetrios Palaiologos had become a man of (soft) power. This case must be understood as the first example of the Greeks’ influence in Northwestern Europe’s societies, which can be associated with the concept of state building. This issue remais rather understudied.